Clinal variation as a tool to understand climate change - Mayekar, Harshad Vijay; Ramkumar, Durga Kavya; Garg, Divita; Nair, Abhishek; Khandelwal, Ashwin; Joshi, Kavya; Rajpurohit, Subhash (Frontiers in Physiology, 2022)
Clines are observable gradients that reflect continuous change in biological traits of species across geographical ranges. Clinal gradients could vary at geographic scales (latitude and altitude). Since clinal variations represent active genomic responses at the population level they (clines) provide an immense power to address questions related to climatic change. With the fast pace of climate change i.e. warming, populations are also likely to exhibit rapid responses; at both the phenotypic and genotypic levels. We seek to understand how clinal variation could be used to anticipate climatic responses using Drosophila, a pervasively used inter-disciplinary model system owing to its molecular repertoire. The genomic information coupled with the phenotypic variation greatly facilitates our understanding of the Drosophilidae response to climate change. We discuss traits associated with clinal variation at the phenotypic level as well as their underlying genetic regulators. Given prevailing climatic conditions and future projections for climate change, clines could emerge as monitoring tools to track the cross-talk between climatic variables and organisms.